International Collaboration on Digital Marketing Materials for the Social Entrepreneurship MSME Community Group of Tri Alam Lestari Waste Bank - Ferli, Ossi; Andriani, Meta; Farhanah, Hanifah; Zahna, Rizka Zahrotul; Nuari, Chozin; Dinanti, Queen; Sitohang, Pebri Monica; Kretap, Kreangkrai; Sihapanya, Kunyarat (Jurnal Pengabdian Masyarakat Formosa, 2023)
International Cooperation between STIE Indonesia Banking School and Khon Kaen Business School Thailand in Waste Bank Management and Digital Marketing for MSMEs Tri Alam Lestari Waste Bank Community. The purpose of this service is to create awareness about waste management and digital marketing skills among MSMEs. This process includes the discussion stage, identification of needs, preparation of materials, and implementation of seminars. The implementation methods include finding expert speakers, presenting material, and question and answer sessions. This activity was carried out in South Jakarta, located at Tri Alam Lestari Waste Bank. As a result, MSMEs' understanding of digital marketing and environmental awareness increased, which has the potential to impact business growth and environmental sustainability.